Legal Politics of Responsive National Education System in the Globalization Era and the Covid-19 Pandemic - Putera Astomo (Yuridika, 2021)
The Government’s serious effort to build a National Education System in anticipating the development and progress of globalization is manifested through making, stipulating and implementing policies related to the education sector. To prevent illegal policies, laws and regulations are needed as a juridical basis for these policies especially during the current Covid-19 pandemic. The making of laws and regulations that pertain to public affairs is called political law. What needs to be emphasized in legal politics is the guarantee of protection for public participation in the formation of laws and regulations. Community participation, if associated with responsive law, implies that the principle of public participation is paramount in the formation of law for the realization of democratic legal products. Responsive legal politics still creates problems due to the lack of public participation in the making of laws and regulations. Therefore, the research problem is whether the legal politics of the National Education System in the era of globalization is responsive or not. To address this problem a normative juridical approach is used. The results show that the responsive legal politics of the National Education System in the era of globalization consists of the following: Law Number 20 of 2003 on the National Education System, Law Number 14 of 2005 on Teachers and Lecturers, Law Number 12 of 2012 on Higher Education, and Circular of the Minister of Education and Culture Number 4 of 2020 on Implementation of Education Policies in the Emergency of Coronavirus Disease (Covid-19) Spreading.